Maximum power point tracking for stand-alone PV system based on artificial intelligence techniques - Salem Bendouiem; Toumi Djaafar; Djilani Benattous; Khechekhouche Ali; Gassem Abdelmalek (University of Eloued, 2023)
maximum power point tracking (MPPT) algorithm lead an important role in optimization the performance of a photovoltaic (PV) generation systems. To validate the correctness and performance of the MPPT techniques, We have created an fuzzy logic (FLC) controller for the maximum power point tracking (MPPT) of a photovoltaic system and compared it to conventional tracking algorithms Perturb and Observe (P&O) and incremental conductance (INC). The proposed system was simulated and tested successfully by using MATLAB Simulink on a photovoltaic solar panel model. It is demonstrated that the fuzzy logic based MPPT tracking require less time and provide more accurate results under rapidly changing atmospheric conditions. compared to conventional tracking algorithms Perturb and Observe (P&O) and incremental conductance (INC)
Intervention
Keywords: Photovoltaic (PV); MPP; Perturb and observe; Simulink; MPPT; Perturb and Observe (P&O); incremental conductance (INC); fuzzy logic; controller; boost converter